Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa STIM LPMI Pada Pembelajaran Portofolio Mata Kuliah Pendidikan Kewarganegaraan - Muhammad Awin Alaby (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to find out how the motivation of regular semester A class A students in Air Transportation Management Study Program. In portfolio learning courses in Citizenship Education. This study uses quantitative methods with questionnaires and documentation as primary data, while observation as supporting data. The research subjects were 21 respondents and were population research. Data obtained from questionnaires and documentation were then analyzed using quantitative methods using simple linear regression. The results of hypothesis testing indicate that the value of t-count is greater than the value of t-table with a significance level of 0.05. The t-count value is 2.141 while the t-table value is 1.720 with db N - 1 = 21 - 1 = 20 (2.141> 1.720) then Ho is rejected, meaning that there is a positive effect between learning motivation and learning achievement in the portfolio of transportation management students air.